The methanolic extract of Guibourtia tessmannii (Caesalpiniaceae) improves sexual parameters in high fat diet-induced obese sexually sluggish rats - Patrick Brice Deeh Defo; Modeste Wankeu-Nya; Esther Ngadjui; Georges Romeo Bonsou Fozin; François Xavier Kemka; Albert Kamanyi; Pierre Kamtchouing; Pierre Watcho (Asian Pacific Journal of Reproduction, 2017)
Objective: To evaluate the effects of the methanolic extract of Guibourtia tessmannii (G. tesmannii) on sperm parameters, lipid profile and testosterone level in obese rats.Methods: A total of 193 male Wistar rats were fed either with palm oil diet (n=185) or standard diet (n=8) for 16 wk. At the end of this feeding period, 90 obese rats were selected and randomly divided into 18 groups of five rats each and treated with distilled water (10 mL/kg), vitamin E (75 mg/ kg), clomiphene citrate (2 mg/kg) or methanolic extract of G. tessmannii (55, 110 or 220 mg/ kg) for 7, 21 or 56 d. At the end of each treatment period, sperm parameters, lipid profile and testosterone level were evaluated. Data were analyzed using ANOVA for repeated measures followed by post-hoc Tukey HSD (P<0.05) for multiple comparisons.Results: Feeding of rats for 16 wk with palm oil diet significantly damaged sperm parameters. The methanolic extract of G. tesmannii improved sperm viability, motility and normality after 21 or 56 d of treatment. The sperm normality increased significantly in rats treated with the methanolic extract of G. tesmannii for 7 (110 mg/kg, P<0.01) and 56 d (110 and 220 mg/kg, P<0.05) compared to control group. Triglycerids, total cholesterol, low and very low density lipoproteins cholesterol levels were lower in rats treated with the plant extract for 56 d. G. tesmannii also significantly increased the high density lipoprotein cholesterol and testosterone levels in the plasma after 56 d of treatment.Conclusions: The methanolic extract of G. tesmannii can improve sperm parameters, lipid profile and testosterone level in obese rats. These findings may justify the folkloric use of G. tesmannii as a reproductive performance enhancer.